Isolation and Purification of the Z-disc from Vertebrate Myofibrils - Samer N. Khalaf (Journal of Global Pharma Technology, 2019)
The Z-disc is located within the I-band between neighboring sarcomeres (the fundamental unit of contraction within the muscle). It is composed of approximately 40 proteins, mostly α-actinin. Recent studies have reported that this part of the sarcomere is an active structure that contributes to the sensing mechanism and signaling pathways that control muscle activity. Several mutations occur in the Z-disc proteins and cause many diseases. In addition, the interactions between these proteins are not understood yet. Thus, many attempts have been made to isolate a well-preserved Z-disc that would help to understand the interactions between its proteins and treatment of different diseases, particularly some cardiac diseases. Different strategies have previously been applied to isolate the Z-disc from insects, for example, but these were harsh conditions that caused damage to the Z-disc. Herein, mild conditions were applied to extract a well-preserved Z-disc from vertebrate myofibrils. Our procedure was primarily based on two steps; homogenisation of myofibrils into A-bands and I-bands after digestion of titin with trypsin, and then depolymerising actin through gelsolin. Phase contrast light microscope, SDS-PAGE analysis and electron microscopy with negative staining were employed for visualization. Myofibrils were prepared successfully in a suitable quality (striated and single myofibrils) and quantity. Titin was cleaved using trypsin and the A-band and I-band were partially separated. Furthermore, our findings showed partially depolymerisation of actin filaments with gelsolin. The mild conditions used were considered a promising start to a successful method for isolation of Z-discs from vertebrates.Keywords: Z-discs, Sarcomere length, Titin, Trypsin, Actin, Gelsolin.